Modeling the relationship between human intelligence, knowledge management practices, and innovation performance - Noordin, Mohamad Fauzan; Karim, Z.A (World Scientific Publishing Co., 2015)
Pioneers in knowledge management (KM) have well articulated the relationship between KM and innovation. In addi- tion, there are many theoretical papers as well as empirical studies that examined the positive relationship between KM and innova- tion. However, these empirical studies analysed the relationship between KM and innovation at management or organisational level. There is a need to study this relationship at the knowledge workers level to see how they actually in°uence their organisational KM and innovation. This study aims to analyse the knowledge worker's intelligence, emotional, and spiritual potential towards KM and innovation as well as examine the relationship between knowledge workers, KM and innovation. Survey questionnaires are used to measure knowledge workers' intelligence quotient (IQ), emotional quotient (EQ), and spiritual quotient (SQ), their KM processes involvement, and perception on their innovation perfor- mance. Partial least square (PLS) analysis is used in the analyses to determine the relationship between human intelligence, KM pro- cesses and innovation performance. Results indicate that human EQ and SQ in°uenced KM and innovation but not IQ.